Predicting Vulnerabilities in the Delivery of Secure Healthcare Supply Chain Services - McBride, Maurice L. (Cybersecurity and Innovative Technology Journal, 2024)
The COVID-19 pandemic exposed the weaknesses in healthcare supply chains, leading to shortages, increased costs, and untrustworthy vendors. This has put patients at risk for treatment delays, worse care, and higher death rates. The healthcare supply chain's dependence on single sourcing has made these issues worse. Geopolitical conflicts, climatic catastrophes, data privacy issues, cybersecurity threats, and counterfeit goods are emerging risks. Resilient solutions are needed due to the complex ecosystem of manufacturers, wholesalers, regulatory organizations, and healthcare providers. Supply Chain Resilience (SCRES) is crucial for uninterrupted healthcare services, with redundancy, visibility, and adaptability being key components. Future research directions include blockchain integration, data analytics, and regulatory frameworks to improve resilience. Successful mitigation solutions require understanding interdependence, resilience measurements, and behavioral elements. Addressing these vulnerabilities is crucial for patient safety and healthcare effectiveness.